2009
DOI: 10.1002/qua.22015
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg states of the helium atom

Abstract: Using the recently introduced maximum overlap method andHartree-Fock Perturbation Theory (HFPT), we compute Hartree-Fock (HF) wavefunctions for triplet 1s ns states of the helium atom. Comparison with near-exact results from Nakatsuji's free ICI method reveals that HF theory provides a simple route to accurate energies of these Rydberg states, especially for large n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…This observation is in agreement with Ref. [43] whose authors pointed out that "In those states where n >> 1, the electrons are spatially well separated and one might anticipate intuitively that they will be weakly correlated and that the x-COEP and Hartree-Fock methods, which neglects such effects, may be an excellent approximation". …”
Section: Results Of Calculations and Their Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This observation is in agreement with Ref. [43] whose authors pointed out that "In those states where n >> 1, the electrons are spatially well separated and one might anticipate intuitively that they will be weakly correlated and that the x-COEP and Hartree-Fock methods, which neglects such effects, may be an excellent approximation". …”
Section: Results Of Calculations and Their Discussionsupporting
confidence: 79%
“…Unlike Ref. [43] our calculations were restricted to 6 states (up to 1s7s) because for n > 7 we observed that the corresponding optimal basis sets present some linear dependencies. We used double precision and controlled the conditionality of the overlap matrix by calculating its eigenvalues in order to avoid the appearance of computational linear dependence.…”
Section: Results Of Calculations and Their Discussionmentioning
confidence: 99%
See 3 more Smart Citations